Adaptive Scheduling Algorithm for the Coexistence of ONUs with Different Tuning Time in Virtual Passive Optical Network - Xingdi Wang; Chaoqin Gan; Liya Tong (IEEE Photonics Journal)
Optical network unit (ONU)'s wavelength tuning time is a key factor that cannot be ignored in ONU scheduling algorithm for multi-wavelengths passive optical network (PON). In this paper, we propose an adaptive scheduling algorithm for the coexistence of ONUs with different tuning time in virtual PON, which is called multi-tuning-time ONU scheduling (MOS) algorithm. The simulation shows that the MOS algorithm can effectively avoid the extra queue delay caused by ONUs’ wavelength tuning and reduce the waste of bandwidth resources.